2009
DOI: 10.1007/s12017-009-8066-1
|View full text |Cite
|
Sign up to set email alerts
|

microRNAs in CNS Disorders

Abstract: In recent years, there has been a shift in the conventional paradigms for transcriptional and translational regulation as extensive sequencing efforts have yielded new insights into the landscape of the human genome and transcriptome. Hundreds of non-coding regulatory RNA molecules called microRNAs (miRNAs) have been identified in the mammalian central nervous system (CNS) and are reported to mediate pivotal roles in many aspects of neuronal functions. Disruption of miRNA-based post-transcriptional regulation … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
55
0

Year Published

2009
2009
2017
2017

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 75 publications
(56 citation statements)
references
References 77 publications
(100 reference statements)
1
55
0
Order By: Relevance
“…Previous studies have shown that stroke also induces changes in the miRNA expression profiles in rodents, as well as humans (30,31) (Table I).…”
Section: Strokementioning
confidence: 90%
“…Previous studies have shown that stroke also induces changes in the miRNA expression profiles in rodents, as well as humans (30,31) (Table I).…”
Section: Strokementioning
confidence: 90%
“…There are over 1000 miRNAs in humans and they are typically measured using either RNA sequencing, microarray, Nanostring, or real-time quantitative polymerase chain reaction methodologies. Alterations in miRNA regulation has been implicated in a wide variety of CNS disorders [110][111][112]. Defects in miRNA biogenesis, for example via knockout of Dicer, has been correlated with decreased motor activity and survival, muscle atrophy, denervation, spinal cord sclerosis, and axonopathy in mice [113].…”
Section: Micrornamentioning
confidence: 99%
“…Several downregulated miRNAs have been demonstrated in the brain, including the miR-107 (9) and miR-29 families (5), which regulate the expression of BACE1 and consequently affect the production of Aβ. Of the presently identified miRNAs, ~70% are expressed in the brain, however, the pathological implications of dysregulated miRNA expression in AD remain to be fully elucidated (10).…”
Section: Introductionmentioning
confidence: 99%